Planting empire, cultivating subjects : British Malaya, 1786-1941 - Lees, Lynn Hollen (Cambridge : Cambridge University Press, 2017)
Planting Empire, Cultivating Subjects examines the stories of ordinary people to explore the internal workings of colonial rule. Chinese, Indians, and Malays learned about being British through the plantations, towns, schools, and newspapers of a modernizing colony. Yet they got mixed messages from the harsh, racial hierarchies of sugar and rubber estates and cosmopolitan urban societies. Empire meant mobility, fluidity, and hybridity, as well as the enactment of racial privilege and rigid ethnic differences. Using sources ranging from administrative files, court transcripts and oral interviews to periodicals and material culture, Professor Lees explores the nature and development of colonial governance, and the ways in which Malayan residents experienced British rule in towns and plantations. This is an innovative study demonstrating how empire brought with it both oppression and economic opportunity, shedding new light on the shifting nature of colonial subjecthood and identity, as well as the memory and afterlife of empire.
Introduction -- The birth of plantation colonialism -- Body politics in a plural society -- New towns on the Malayan frontier -- Urban civil society -- Rubber reconstructs Malaya -- Cosmopolitan modernity -- Managing Malayan towns -- Multiple allegiances in a cosmopolitan colony -- Epilogue: representing empire, remembering colonial rule.
Title from publisher's bibliographic system (viewed on 05 Jan 2018).
Keywords: Plantations -- Malaysia -- Malaya -- History; Agriculture and politics -- Malaysia -- Malaya -- History; Cosmopolitanism -- Malaysia -- Malaya -- History; Imperialism -- Social aspects -- History; Malaya -- History -- British rule, 1867-1942.